2010
DOI: 10.1159/000322121
|View full text |Cite
|
Sign up to set email alerts
|

Improved Visual Hallucination by Donepezil and Occipital Glucose Metabolism in Dementia with Lewy Bodies: The Osaki-Tajiri Project

Abstract: Deficits in the cholinergic system are pronounced in dementia with Lewy bodies (DLB) and are more severe in patients with visual hallucinations (VHs). The aim is to identify the occipital glucose metabolism patterns by positron emission tomography (PET) and the changes following donepezil treatment. 13 DLB patients with VHs were enrolled in the study. After the first FDG-PET study, 5 mg/day donepezil was administered orally, and a second PET study was performed 3 months later. After donepezil administration, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 47 publications
2
24
1
Order By: Relevance
“…In the context of DLB, previous FDG-PET studies revealed a pattern of hypometabolism in the medial occipital cortex (Klein et al, 2010;Perneczky et al, 2008a;Satoh et al, 2010), in agreement with the previously reported SPECT data of hypoperfusion. Furthermore, other literature data found a correlation between cerebral hypometabolism in right temporoparietal cortex, prefrontal cortex and the precuneus and patients' performance level of everyday competence (Perneczky et al, 2008b;Perneczky et al, 2009a).…”
Section: Positron Emission Tomography (Pet)supporting
confidence: 90%
“…In the context of DLB, previous FDG-PET studies revealed a pattern of hypometabolism in the medial occipital cortex (Klein et al, 2010;Perneczky et al, 2008a;Satoh et al, 2010), in agreement with the previously reported SPECT data of hypoperfusion. Furthermore, other literature data found a correlation between cerebral hypometabolism in right temporoparietal cortex, prefrontal cortex and the precuneus and patients' performance level of everyday competence (Perneczky et al, 2008b;Perneczky et al, 2009a).…”
Section: Positron Emission Tomography (Pet)supporting
confidence: 90%
“…These studies found that donepezil decreased the severity of hallucinations, but found conflicting imaging results, with one reporting occipital perfusion increased after treatment, (Mori et al 2006) but the other decreased glucose metabolism (Satoh et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…13,26,27 In DLB, occipital hypometabolism correlates with visual hallucinations 28 and improves with acetylcholinesterase inhibitor treatment. 29 The occipital hypometabolism in DLB is independent of Ab load 11 and is thought to be related to impaired cholinergic transmission or synaptic dysfunction associated with a-synuclein. [30][31][32] In addition, occipital hypometabolism is characteristic of posterior cortical atrophy (atypical AD) and advanced AD and thus is not specific for DLB.…”
Section: Antemortemmentioning
confidence: 99%